Proceedings of the Fourth Euro-China Conference on Intelligent Data Analysis and Applications (Advances in Intelligent Systems and Computing,, 2018)
This book highlights recent advances in intelligent data analysis, computational intelligence, signal processing, and all associated applications of artificial intelligence. It gathers papers presented at the ECC 2017, the Fourth Euro-China Conference on Intelligent Data Analysis and Applications. The aim of the ECC was to provide an internationally respected forum for scientific research in the broad areas of intelligent data analysis, computational intelligence, signal processing, and all associated applications of artificial intelligence (AI). The fourth installment of the ECC was jointly organized by the University of Málaga, Spain; the VŠB - Technical University of Ostrava, Czech Republic; and Fujian University of Technology, Fuzhou, China. The conference took place in Málaga, Spain on October 9-11, 2017.